The Relationship Between Stroke Repetition and Some Physiological Indicators of 100m Breaststroke Swimmers Aged 13 – 14 Years - Abdul Jabbar, Farqad (Journal of Physical Education, 2016)
The importance of the research lies in identifying the relationship between stroke frequency and some physiological indicators of 100m breaststroke swimmers aged 13 – 14 years old. The problem of the research lies in answering the following question; is there a relationship between stroke frequency and the some physiological indicators (pulse, PEF, FEV1) in 13 – 14 years old swimmers. The aim of the research is to identify the relationship between stroke frequency rate and some physiological indicators of 100m breaststroke swimmers. The researchers hypothesized a statistical relationship betweenstroke frequency and some physiological indicators of 100m breaststroke swimmers aged 13 – 14 years old. The researcher used the experimental method. The subjects were (10) breaststroke swimmers from all Baghdad swimming clubs (Al Jaish, Al Shorta, Al Selam, Al Kadhmia, and Al Adamia) aged 13 – 14 years old. Two swimmers were selected from each club. 100m breaststroke swimming test was applied and stroke frequency, pulse, PEF, and FEV1. After conducting the statistical operations the researcher concluded that there is a strong relationship between stroke frequency and some physiological indicators in 100m breaststroke swimmers, and that this relationship is a natural result of artistic and motor performance in breaststroke. Finally the researcher recommended using stroke frequency as a mechanical indicator during training process as well as using modern apparatuses for measuring physiological indicators.